TRENDS OF WORLD COAL MINING DEVELOPMENT AND THERMAL POWER GENERATION - PIVNYAK, Gennadiy; SHASHENKO, Olexandr (My University, 2018)
On the base of studying the current situation in the world mining and energy generation authors make the prognosis of these sectors development and involving new methods of the “Technology 5,0”.
Keywords: mining technologies; energy generation; synchro-mining; ecological and economic indicators